Role of Community Group Exposure in Reducing Sexually Transmitted Infection-Related Risk among Female Sex Workers in India - Yadav, Diwakar (Public Library of Science, 2013)
BACKGROUND: Empowering female sex workers (FSWs) to address structural barriers and forming community groups (CGs) through community mobilization are seen as essential components of HIV prevention programs in India. Taking the membership of a CG as an exposure intervention, we hypothesized whether participation in a CG lead to reduced sexually transmitted infections (STIs) and increased treatment-seeking behavior among FSWs in three selected states of India — Andhra Pradesh, Maharashtra and Tamil Nadu. METHODS AND FINDINGS: The propensity score matching (PSM) approach examined the effect of CG membership, as against no membership, on STI-related risk, described as selected outcome measures — presence of any STI, self-reported STI symptoms, and treatment-seeking behavior among FSWs. A cross sectional bio-behavioral survey was administered in 2009–2010 and covered 7,806 FSWs through two-stage probability-based conventional and time location cluster sampling in 23 administrative districts of Andhra Pradesh, Maharashtra and Tamil Nadu. Only 2,939 FSWs were reported to be members of a CG and among them 4.5% had any STIs. A majority of FSWs were aged above 24 years (86.4%), had ever been married (73%), operated from a public place for solicitation (81.5%), and had ever received HIV test results (75.6%). The average effect of CG exposure was reduction in STI prevalence by 4%, while self-reported STI symptom treatment-seeking behavior increased by 13.7%. CONCLUSION: FSWs who were exposed to a CG were at a substantially lower risk of STIs than those who were unexposed. The FSWs exposed to a CG had a higher chance of seeking STI treatment from public and private health facilities. Collectivization related challenges must be overcome to provide access to tailored STI prevention and care services.